Urolithin A increases the natural killer activity of PBMCs in patients with prostate cancer - Rogovskii, Vladimir; Murugin, Vladimir V.; Vorobyev, Nikolay; Popov, Sergey; Sturov, Nikolay; Krasheninnikov, Alexey; Morozov, Alexander; Prokhorova, Marina (Frontiers in Pharmacology, 2025)
BackgroundThe natural killer (NK) activity of peripheral blood mononuclear cells (PBMCs) is a crucial defense against the onset and spread of cancer. Studies have shown that patients with reduced NK activity are more susceptible to cancer, and NK activity tends to decrease due to cancer-induced immune suppression. Enhancing the natural cytotoxicity of PBMCs remains a significant task in cancer research.MethodsThis study investigates the potential of urolithin A, a polyphenolic metabolite produced by the gut microbiota, to enhance the natural cytotoxicity of PBMCs in prostate cancer patients and healthy subjects. We investigated the possible role of aryl hydrocarbon receptor (AhR) in this capability of urolithin A. We analyzed the ability of PBMCs preincubated with urolithin A, AhR agonist or antagonist to kill K562 (human chronic myelogenous leukemia) target cells.ResultsOur results demonstrate that urolithin A enhances the natural cytotoxicity of PBMCs in a dose-dependent manner. Specifically, at a concentration of 10 μM, urolithin A increased the NK activity of PBMCs from prostate cancer patients by an average of 23% (95% CI, 7%–38%). In addition, urolithin A modulates the level of cytokine production by PBMCs, decreasing the level of fractalkine, IL-8, and MCP-3. An AhR antagonist (CH223191, 1 μM) also increased NK activity, while an AhR agonist (β-naphthoflavone, 10 μM) did not increase NK activity and partially inhibited the urolithin A-induced enhancement.ConclusionUrolithin A increases the NK activity of PBMCs from patients with prostate cancer and healthy subjects, and the AhR may be involved in this capability of urolithin A.